Ḥalālan Ţhayyiban Food in the Qur’an and The School’s Role in Ensuring Students’s Nutrition and Healthy Food - Rahardja, Muhammad Nurfaizi Arya; Hakim, Faisol; Ariasti, Widya; Heriansah, Heriansah; Supriadi, Udin (JOURNAL OF QUR'AN AND HADITH STUDIES, 2024)
This research aims to analyze the concept of ḥalālan ṭayyiban food in the Qur'an and school policies in ensuring nutrition and healthy food for students. This study employs a multi-method design involving both library and field studies. The library study uses a tahlili interpretation method to analyze the concept of ḥalālan ṭayyiban, while the field study examines school policies. Data collection techniques include observation, interviews, document analysis, and the review of Qur'anic verses and related interpretations. Data were analyzed descriptively through reduction, presentation, and conclusion techniques. The findings indicate that ḥalālan ṭayyiban not only pertains to permissibility but also to nutritional value and food healthiness. Schools play a vital role in ensuring students consume ḥalālan ṭayyiban food through policies such as outreach, canteen monitoring, and collaboration with parents.